Association between the presentation of endometritis and serum calcium levels in dairy intensive cattle (Lima, Peru) - Arévalo R., Irma (2021)
The aim of the research was to study the association between the presentation of endometritis and serum calcium levels in intensively reared dairy cows from Lima, Peru. The study was carried out with 76 Holstein cows. Blood samples were taken on the seventh day of parturition to measure calcium levels using a spectrophotometer, considering 8 mg/dl as the threshold to determine the presence of subclinical hypocalcemia. The diagnosis of endometritis was made at 35 ± 3 days postpartum using the commercial Metricheck® device to evaluate the appearance of vaginal fundus discharge, considering as endometritis a score greater than or equal to 2 on the McDougall scale. A significant difference was found between multiparous cows with and without hypocalcemia in the presentation of endometritis (p<0.02), showing 1.65 times more probability of presenting endometritis than animals with normocalcemia. It is concluded that there is an association between the presentation of endometritis in multiparous cows with subclinical hypocalcemia.